2021
DOI: 10.1111/aogs.14073
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact and social support in pregnant women during lockdown due to SARS‐CoV2 pandemic: A cohort study

Abstract: Introduction Anxiety and depression during pregnancy can lead to adverse maternal and neonatal outcomes. The SARS CoV‐2 pandemic, and the complete lockdown required during the first wave in most countries are stressors for pregnant women and can lead to anxiety and depression during pregnancy. The aim of this study was to explore depression and anxiety symptoms, and social support in pregnant women during the SARS CoV‐2 lockdown, as well as to explore demographic risk factors. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 29 publications
9
47
0
1
Order By: Relevance
“…Partner support is a well-known protective factor against depression during the perinatal period [59][60][61][62], especially in times of crisis and stress [63]. These results are consistent with reports of pregnant women during the COVID-19 pandemic that demonstrate higher perceived social support was associated with less depressive symptoms [21], whereas a lack of social support was related to increased risk for perinatal depressive symptoms [64]. In a mixed-methods pilot study from the US, pregnant women who reported feelings of isolation and loneliness also reported that partner support was the most important protective factor which helped them to cope with the pandemic [33].…”
Section: Discussionsupporting
confidence: 85%
“…Partner support is a well-known protective factor against depression during the perinatal period [59][60][61][62], especially in times of crisis and stress [63]. These results are consistent with reports of pregnant women during the COVID-19 pandemic that demonstrate higher perceived social support was associated with less depressive symptoms [21], whereas a lack of social support was related to increased risk for perinatal depressive symptoms [64]. In a mixed-methods pilot study from the US, pregnant women who reported feelings of isolation and loneliness also reported that partner support was the most important protective factor which helped them to cope with the pandemic [33].…”
Section: Discussionsupporting
confidence: 85%
“…73). 26 It is important to note that for the aforementioned studies 25 , 26 the sample was recruited in the hospital setting, unlike our study where they were recruited online. In a study conducted in Israel, it was observed that one of the most important sources of anxiety during the COVID-19 pandemic in pregnant women was attending pregnancy check-ups and being in public places.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women, who experience major physical and psychological changes, are a vulnerable population during the COVID-19 epidemic. The infection threat may cause stress on perinatal women and negatively influence their psychological health 1 . Home quarantine increases inconvenience of perinatal women's antenatal examinations, which might also negatively affect their psychological status.…”
Section: Introductionmentioning
confidence: 99%